An Assessment on Solar Cell Parameter Estimation, Deposition Techniques, Physical Properties, Application and Challenges - Ashu Chouhan , Amandeep Sharma (International Journal of Advanced Science and Technology, 2020)
Solar power is rapidly gaining industry and academia's focus. This intense emphasis is motivatedprimarily by the task of transitioning to the alternative of fossil fuels and reducing environmentalpollution caused by their emissions. Solar photovoltaic (PV) is a major attractive supplier to thegroup of electricity among all other forms of renewable energy. Modeling their electrical analogcircuits simulates the behavior of PV cells. To describe the activity of PV cells and the amount ofsunlight that is transformed into electricity. Researchers are highly attracted towards "Parameterestimation problem of PV cell model" to preside over circuit design solar cell parameters. This reviewpaper discusses the old and new methods to optimization used to predict parameters of PV cells andto test their output for various circuit designs.